An Update of Medical Nutrition Therapy in Gestational Diabetes Mellitus - Flavia Cristina Vasile; Agnesa Preda; Adela Gabriela Ștefan; Mihaela Ionela Vladu; Mircea-Cătălin Forțofoiu; Diana Clenciu; Ioan Ovidiu Gheorghe; Maria Forțofoiu; Maria Moța (Journal of Diabetes Research)
Gestational diabetes mellitus (GDM) is a serious and frequent pregnancy complication that can lead to short and long-term risks for both mother and fetus. Different health organizations proposed different algorithms for the screening, diagnosis, and management of GDM. Medical Nutrition Therapy (MNT), together with physical exercise and frequent self-monitoring, represents the milestone for GDM treatment in order to reduce maternal and fetal complications. The pregnant woman should benefit from her family support and make changes in their lifestyles, changes that, in the end, will be beneficial for the whole family. The aim of this manuscript is to review the literature about the Medical Nutrition Therapy in GDM and its crucial role in GDM management.